2007
DOI: 10.1093/rpd/ncm482
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Regulatory Authority low energy germanium detection system: performance for the uranium individual monitoring

Abstract: The lung counter facility of the Nuclear Regulatory Authority (ARN) is presented. A calibration was carried out using the Lawrence Livermore National Laboratory (LLNL) phantom. This phantom is provided with a pair of lungs and lymph nodes containing uranium homogeneously distributed and a set of four overlay plates covering a chest wall thickness (CWT) ranging from 1.638 to 3.871 cm. Individual organ calibration factors were acquired for 235U photopeaks energies and for each effective chest thickness. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Consequently, an internal source of activity is seldom limited to one organ or to one body region but rather follows a time-dependent distribution among different organs. Several studies have already demonstrated the influence of the biokinetics on in vivo counting by experimental means (Spinella et al 2007) and by Monte Carlo simulation in voxel phantoms (Hunt et al 2003;de Carlan et al 2007). However, no general method has been available to practically take this information into account for calibration of in vivo counting systems currently in use by health physics laboratories.…”
Section: A Recent Improvement Of Oedipe: Implementation Of the Biokinmentioning
confidence: 99%
“…Consequently, an internal source of activity is seldom limited to one organ or to one body region but rather follows a time-dependent distribution among different organs. Several studies have already demonstrated the influence of the biokinetics on in vivo counting by experimental means (Spinella et al 2007) and by Monte Carlo simulation in voxel phantoms (Hunt et al 2003;de Carlan et al 2007). However, no general method has been available to practically take this information into account for calibration of in vivo counting systems currently in use by health physics laboratories.…”
Section: A Recent Improvement Of Oedipe: Implementation Of the Biokinmentioning
confidence: 99%